Tuberculosis and multi-drug resistant tuberculosis: immunologic mechanisms and tools for controlling the disease - DOI: 10.3395/reciis.v2i1.132en - Roberta Olmo Pinheiro; Margareth Pretti Dalcolmo; Elizabeth Pereira Sampaio (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2008)
It is estimated that one third of the world's population is infected with Mycobacterium tuberculosis. In 2005, the World Health Organization estimated that eight million people died from tuberculosis worldwide. The official indicators point to a decline in tuberculosis rates in the past century but since 1990 the incidence rates are increasing again. Despite the existence of medicines effective in the control of tuberculosis, the cases of multi-drug resistance have increased worldwide. Recently the problem became even worse with the emergence of strains extremely resistant to drugs, responsible for what the WHO calls XDRTB (extensively drug resistant tuberculosis). The only vaccine available against this disease, the BCG vaccine, is efficient in preventing severe forms of tuberculosis in children. Its efficiency in adults however varies considerably and it has been demonstrated that revaccination does not increase the degree of protection in adolescents and adults. Various studies demonstrated that, in the attempt to contain the infection, the host cells develop immunoregulatory and mycobactericide mechanisms, and that failures in these mechanisms allow the disease to advance. The aim of this article is to review the data related to the immune response in patients with tuberculosis and multi-drug resistant tuberculosis (MDR-TB) and to show how these findings can contribute to the development of new diagnostic strategies and/or vaccines to control the disease.